Pengembangan Media Pembelajaran Respiratory Card menggunakan Model Pembelajaran Project Based Learning pada Materi Sistem PernapasanÂ Manusia - Silitonga, Aida Natalia; Muchtar, Zainuddin (Lensa: Jurnal Kependidikan Fisika, 2025)
Active learning should involve students directly in the learning process through interaction with peers and teachers. However, classroom instruction often fails to engage students effectively, with limited use of varied instructional media and models. This study aims to develop a Respiratory Card learning medium using the Project-Based Learning (PjBL) model to improve learning outcomes of fifth-grade elementary school students on the topic of the human respiratory system. This research employed a Research and Development (R&D) approach using the 4D development model, which includes the stages of Define, Design, Develop, and Disseminate. Data collection techniques included interviews, observations, questionnaires, and tests, while data were analyzed qualitatively and quantitatively. The results showed that: (1) the Respiratory Card learning media was declared valid with average scores of 88% from content experts and 90.6% from media experts, categorized as â€œhighly feasibleâ€ using a Likert scale; (2) the media was considered practical based on a 92% average score from teacher responses, categorized as â€œvery practicalâ€; and (3) the media was effective, as indicated by an improvement in studentsâ€™ test scores to an average of 84.2% at SDS Attaufiq Medan, and significant differences were found in learning outcomes between the experimental and control classes at UPT SDN Percobaan (sig. value = 0.000 < 0.05). The use of the Respiratory Card media enhanced student engagement and improved learning outcomes.